Comparison of Conventional Ferguson’s Haemorrhoidectomy with Ligasure Haemorrhoidectomy focusing on complications and hospital stay: Single Institutional Study - Ragavendra, J.; Ahamed, A. Kazzali; Ramula, M.; Megha. A, M. S., Saroja; Pooja, S.; Ul Hameed, Fareed (Journal of Neonatal Surgery, 2025)
Background: Ligasure haemorrhoidectomy and Ferguson's haemorrhoidectomy are two popular surgical techniques used to manage haemorrhoids, especially grade III and IV cases. Based on available studies, Ligasure Haemorrhoidectomy uses a vessel-sealing system to coagulate the pedicle of the haemorrhoid instead of conventional ligation and cutting. The advantage of the less operating time, compared to conventional Ferguson's method, where trans fixation and excision need more time. Additional advantages include less postoperative pain, blood loss, and shorter hospital stay. Objective: To compare Conventional Ferguson’s Haemorrhoidectomy with Ligasure Haemorrhoidectomy, focusing on complications and hospital stay Methods: Prospective single-blinded randomised control study, conducted in the Department of Surgery, with 50 consecutive patients presenting with grade III and IV haemorrhoids. Purposive sampling, taken from the study frame of haemorrhoid patients for a period of one year from January 2024 to December 2024. Patients were divided by simple computer randomisation into 2 groups for two different techniques. One group of 25 patients consented to Ligasure haemorrhoidectomy, and 25 patients opted for Ferguson’s haemorrhoidectomy without using Ligasure. Results: Our study on 50 patients shows that, compared to Ferguson’s method, Ligasure™ haemorrhoidectomy had a shorter operating time of around 15 minutes, compared to Ferguson’s method, which takes more than 30 minutes for the same procedure. Blood loss (20 vs 10 ml), less postoperative pain as measured using the Visual analogue scale, with fewer postoperative complications, including retention of urine and wound dehiscence (18% vs 12%). The most important advantage being less hospital stay and early recovery. Conclusion: Ligasure coagulates the pedicle of the haemorrhoids in less time, with limited lateral spread of energy without the need for suturing. Fewer post-operative complications in terms of pain, bleeding, and shorter hospital stay compared to Ferguson’s method. The easy application, in a shorter time, with minimal post-operative complications and fewer hospital days, makes Ligasure a preferred method over the Ferguson procedure.